An Application of the Disequilibrium Adjustment Framework to Small Area Forecasting and Impact Analysis - Geoffrey Hewings; Jae Hong Kim (European Regional Science Association (ERSA), 2011)
The disequilibrium adjustment frameworks, pioneered by Carlino & Mills (1987) and further extended by Boarnet (1994a), have been widely adopted by various regional and intra-regional studies, 1) determining whether jobs follow people or people follow jobs or the both; 2) examining the determinants of growth or location decisions; and 3) investigating spread versus backwash effects. Beyond these traditional uses of the framework, this chapter presents an idea of using the model for small area population and employment forecasting and impact analysis. An application using data for the Chicago metropolitan area reveals that the framework, capturing spatial population-employment interaction and adjustment processes, can be a powerful small area forecasting and impact analysis tool, when it is combined with a regional economic forecasting method. Particularly, the spatial econometric specification of the model facilitates the integration of horizontal (across spatial units) as well as vertical (over the hierarchy; macro and sub-regional) dimensions to the analysis of change. This study also discusses some theoretical issues and methodological challenges in this type of application.
Keywords: 330; Small-areas Forecasting; Spatial Adjustment; Econometric Input-Output Model